The Impact of E-procurement on Organisation's Supply Chain Efficiency: A Case Study at the Office of the Auditor General - Ivan Taremwa (Uganda Christian University, 2025)
This study examined the impact of E-Procurement on the effectiveness of supply chains focusing on cost savings, process enhancements, and the management of supplier relationships in the public sector of Uganda specifically targeting the Office of the Auditor General to acquire valid information about the topic of study. As supply chains become increasingly complex through globalization, e-procurement platforms have facilitated greater transparency and streamlined purchasing processes, thereby simplified decision-making for organizations. The research employed a mixed-methods approach, incorporating qualitative case studies alongside quantitative data analysis to evaluate key performance indicators essential for both the initiation and ongoing use of e-procurement in OAG’s procurement operations. Conducted between January and April 2025 with a review of literature from 2003 to 2023, the study assessed various e-procurement techniques, including e-supplier management, e-invoicing, and e-payment, and their impacts on inventory management, cost reduction, risk management, supplier coordination, and lead times. The findings from the selected 80 employees of OAG who are directly involved with the use of e-procurement indicated that it enhanced supply chain efficiency by reducing procurement cycle times and minimizing human errors, fostered improved collaboration with key stakeholders and greatly reduced on operational costs with the organization. However, challenges such as cybersecurity threats, user acceptance, and system integration remain significant . The research concluded with providing strategic recommendations aimed at maximizing the benefits of e-procurement within the organization’s dynamic supply chains.
Undergraduate